Rotatory nystagmus after granisetron administration - Abdulelah Shafiq Abualfraj; Ammar Ismail; Azzah Aljabarti; Maan Jamjoom (Saudi Journal of Emergency Medicine, 2021)
Background: Granisetron is a popular antiemetic medication used in the emergency department to control nausea and vomiting with an excellent side effect profile among adults and pediatric, in both healthy and oncology patients. Case Presentation: Our patient received granisetron for nausea and vomiting then developed torsional nystagmus, asymmetrical abnormal muscle contractions, and electrocardiography showed QTc prolongation 487 ms. The patient did improve after IV lorazepam and magnesium sulphate administration. Conclusion: QTc prolongation increases the risk of developing Torsades de Pointes and sudden death. Extrapyramidal syndrome caused by granisetron is rare and should not be confused with seizure. Both are significant effects associated with 5-HT3 antagonists administration to be aware of and if they occurred, should be managed in a timely fashion. [SJEMed 2021; 2(1.000): 96-101]